2018
DOI: 10.1101/425322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

REC114 partner ANKRD31 controls number, timing and location of meiotic DNA breaks

Abstract: Double-strand breaks (DSBs) initiate the homologous recombination that is crucial for meiotic chromosome pairing and segregation.Here we unveil mouse ANKRD31 as a lynchpin governing multiple aspects of DSB formation. Spermatocytes lacking ANKRD31 have altered DSB locations and fail to target DSBs to sex chromosomes' pseudoautosomal regions (PAR). They also have delayed/fewer recombination sites but, paradoxically, more DSBs, suggesting DSB dysregulation. Unrepaired DSBs and pairing failures-stochastic on autos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(64 citation statements)
references
References 85 publications
(91 reference statements)
4
60
0
Order By: Relevance
“…We found that the PAR was highly enriched for DSB-promoting factors REC114, MEI4, MEI1, and IHO1 [proteins essential for genomewide DSB formation (22-24, 29)] as well as ANKRD31, a REC114 partner essential for PAR DSB formation (30,31). All five proteins (hereafter RMMAI for simplicity) colocalized in several bright, irregular "blobs" for most of prophase I (Fig.…”
Section: A Distinctive Par Ultrastructure Rich In Pro-dsb Factorsmentioning
confidence: 93%
See 4 more Smart Citations
“…We found that the PAR was highly enriched for DSB-promoting factors REC114, MEI4, MEI1, and IHO1 [proteins essential for genomewide DSB formation (22-24, 29)] as well as ANKRD31, a REC114 partner essential for PAR DSB formation (30,31). All five proteins (hereafter RMMAI for simplicity) colocalized in several bright, irregular "blobs" for most of prophase I (Fig.…”
Section: A Distinctive Par Ultrastructure Rich In Pro-dsb Factorsmentioning
confidence: 93%
“…5D). [Ankrd31 -/mutants form substantially fewer RPA2 foci and other cytological DSB markers at leptonema and early zygonema, but not from mid-zygonema on (30,31).] As a consequence, the X and Y chromosomes were paired in only 6% of mid-pachytene spermatocytes ( Fig.…”
Section: Determinants Of Par Dsb Formation In Spermatocytesmentioning
confidence: 98%
See 3 more Smart Citations